The reconstruction of high-pt photons with the electromagnetic calorimeter of the ALICE experiment at the LHC - Gray, Heather M (Department of Physics, 2025)
In two years, the frontier of relativistic heavy ion physics will move to the Large Hadron Collider (LHC), which will explore matter with energy densities greater than 10 times that at the Relativistic Heavy Ion Collider (RHIC), providing an opportunity to test predictions of Quantum Chromodynamics (QCD). At the LHC, the cross-sections for high momentum processes are expected to be sufficiently large for jet physics to play an important role. Some first hints of this exciting physics have already been reported at RHIC energies, namely observation of jet quenching, as indicated by the suppression of the yield of high Pt hadrons and the suppressed yield of back-to-back correlated hadrons from jets, in central Au+Au collisions. However, careful jet and jet quenching analyses require calibration with the parton energy prior to its passage though the nuclear matter. This can only be obtained via analysis of 1 -jet processes because photons, once produced, are essentially unaffected by a colour-charged medium, and pass through the medium retaining their original energy. The experimental challenges include identifying photons within the high multiplicity heavy-ion environment and reducing the background from the photonic decays of neutral pions. This thesis details algorithms developed for photon reconstruction in the heavy-ion envi-ronment for the electromagnetic calorimeter (EMCal) of the ALI experiment. Shower shape analysis was used to optimise cuts to discriminate between the direct photon signal and the background from the photonic decays of neutral pions. Photon energy resolution of approxi-mately 5% at 10 GeV and 3% at 30 GeV was obtained in simulations. An enhancement in the ratio by a factor of 50 relative to theoretical predictions at 20 GeV was obtained using the techniques of shower shape analysis